Fantu Cheru: An Obituary (1949–2026): CODESRIA Bulletin Online, No. 3, June 2026 - Cyril Obi; Carin Norberg; Lennart Wohlgemuth (CODESRIA Bulletin, 2026)
Professor Fantu Cheru was an internationally respected African intellectual and policy-thinker, teacher and mentor. He dedicated his career to producing an intellectual agenda and a transformative policy framework for resolving Africa’s complex development challenges. In his quest for change, he observed that this project was multidimensional and that conventional economic development orthodoxies were inadequate, which made him strongly committed to Africa’s renewal and influenced the core of his lifelong work. As research director at the Nordic Africa Institute (NAI) (2007 to 2012), Professor Fantu Cheru helped to reorganise research, knowledge production and publications at NAI, and produced a blueprint for the Swedish government to help tackle Africa’s developmental challenges in the 21st century. He also played an important role as a bridge between Africa and the Nordic countries, and projected the institute as a friend and partner-in-progress. A scholar of prominent global standing, he went on to take other senior research posts, at the African Studies Centre Leiden (ASCL) in the Netherlands and the Stockholm Institute for Peace and International Affairs (SIPRI), and was a professor-of-practice supporting doctoral training at the University of Bahir Dar in Ethiopia. Fantu Cheru’s illustrious achievements at these institutions were remarkable given his background. Born in Gondar, Ethiopia, in 1949, at one point he supported his family as a shepherd. His early schooling was in Ethiopia. Driven by his passion for education, he later travelled to the United States to continue his education, and obtained a PhD in Political Economy and Urban Planning from Portland State University. He taught at several US universities, including American University, Washington DC, from 1984 to 2007, rising to the rank of Professor of African and Developmental Studies. Apart from his academic research and teaching career, Prof. Cheru held several high-profile positions, including membership of the UN Secretary-General’s Advisory Panel on Mobilizing International Support for the New Partnership for African Development (NEPAD); convenor of the Global Economy Track of the Helsinki Process on Globalization and Democracy; and UN Special Rapporteur on Foreign Debt and Structural Adjustment Programmes, Commission of Human Rights. In addition, he was an advisor and consultant to several governments and multilateral and regional organisations, including the UN and some of its agencies, such as UNECA, UNDP, UN Habitat and UNSO. Prof. Cheru also held consultancies at international development agencies such as ECA, ADF, DANIDA, NORAD and SIDA. He published many books and scholarly articles, including pathbreaking works on globalisation, democratisation and African development, and on Africa and emerging powers. On the latter subject, he edited two important books: The Rise of China and India in Africa: Challenges, Opportunities and Critical Interventions (with Cyril Obi) (London: Zed Books, 2010) and Agricultural Development and Food Security in Africa: The Impact of Chinese, Indian and Brazilian Investments (with Renu Modi) (London: Zed Books, 2013). This was complemented by his co-edited book on The Oxford Handbook on the Ethiopian Economy (with Christopher Cramer and Arkebe Oqubay), published in 2019. His remarkable journey from shepherd boy to the apex of global scholarship and policy engagement reflected his intellectual prowess and commitment to placing his knowledge at the service of ordinary people. Prof. Cheru’s academic leadership and vision for African development and unity was evident in his policy-engaged research, which was strongly driven and underlined by his personal experiences and principles, and firm commitment to the continent’s growth and transformation and the emancipation of its people. Beyond his scholarly writing and high-level policy engagements, he was a great teacher and mentor, and a steadfast promoter of homegrown heterodox economic thinking, African unity and integration, while actively supporting research capacity-building for African doctoral students and early-career scholars. Working with CODESRIA, OSSREA, the SSRC’s African Peacebuilding and Developmental Dynamics (APDD) programme and universities across the continent, including in Ethiopia, he lent his energy and vision to inspiring and nurturing research excellence in the next generation of African scholars. Prof. Fantu left behind a great legacy built on integrity, humane principles, forthrightness, simplicity and transformative thinking for driving Africa’s development and the wellbeing of the African people—those often marginalised and oppressed by dominant elites and externally imposed policies. He passed away in Stockholm on 31 May 2026, and will be greatly missed by his family—wife Annika, and their children Malkolm and Makeda— and friends, colleagues and former students.